(untitled) (RuMoRes, 2010)
The present article introduces the concept of shattered entertainment as to apprehend, in our field of study, certain media narratives (soap operas, reality shows and some movies) that, regarding their reduction as fiction, open space for the debate of political, social and cultural issues in direct relationship to what is circumstantial. Such aspect of our entertainment, detached from its usual definition – as being a folded and independent world, disengaged from educational attempts – is examined considering the historical specificity of our mediatization process. It was forged in the blend of the media into social life and as they did not exactly find resistance from the European-like literate culture and in the failure of traditional apparatus to grant citizenship (as, for example, the educational system), the media assume – and/or is trusted to them – a pedagogic role.